Radical-induced hetero-nuclear mixing and low-field 13C relaxation in solid pyruvic acid. Issue 46 (16th November 2022) - Kouřilová, Hana; Jurkutat, Michael; Peat, David; Kouřil, Karel; Khan, Alixander S.; Horsewill, Anthony J.; MacDonald, James F.; Owers-Bradley, John; Meier, Benno
Abstract : Radicals are a polarization source in dynamic nuclear polarization at high field, but are known to act as polarization sink at low field. Here we show that at intermediate fields radicals can facilitate hetero-nuclear 1 H– 13 C polarization transfer. Abstract : Radicals serve as a source of polarization in dynamic nuclear polarization, but may also act as polarization sink, in particular at low field. Additionally, if the couplings between the electron spins and different nuclear reservoirs are stronger than any of the reservoirs' couplings to the lattice, radicals can mediate hetero-nuclear polarization transfer. Here, we report radical-enhanced 13 C relaxation in pyruvic acid doped with trityl. Up to 40 K, we find a linear carbon T 1 field dependence between 5 mT and 2 T. We model the dependence quantitatively, and find that the presence of trityl accelerates direct hetero-nuclear polarization transfer at low fields, while at higher fields 13 C relaxation is diffusion limited. Measurements of hetero-nuclear polarization transfer up to 600 mT confirm the predicted radical-mediated proton–carbon mixing.